Impacts of COVID-19 Pandemic on Micro and Small Enterprises: Evidence From Rural Areas of Iran - Yaghoubi Farani, Ahmad; Sepahvand, Fatemeh; Gholamrezai, Saeed; Azadi, Hossein; Nazemi, Neda (Frontiers in Public Health, 2022)
Since 2020, the outbreak of the COVID-19 crisis has caused a great deal of social and economic damages to micro and small-scale enterprises (MSEs). This research examined the most common damages of this crisis in active and inactive rural MSEs and also assessed different kind of responses the managers and owners of theses MSEs have received dealing with these damages. The sample population of this study consisted of all managers of 72 active and 38 closed rural MSEs in the Dastjerd village, Hamedan, Iran. These MSEs were mainly garment small factories. This research utilized a mixed approach (quantitative-qualitative) to study the research objectives in depth. First, in qualitative part, semi-constructed interviews and field visits were done. Then, using quantitative, results of the qualitative section, previous studies and the existing literature, a researcher-made questionnaire was created. Based on qualitative part information through interviews, damages of rural MSEs during Covid-19 pandemic were categorized into three classes, including damages related to production, and financial and marketing issues. Also, two categories of managers’ responses that could be labeled as passive and adaptive behavior were identified. Findings showed that active rural MSEs have taken more adaptive measures and tried to find appropriate ways to reduce or overcome damages. Active MSEs were mainly owned and managed collaboratively by more literate and experienced managers. Also results revealed that rural MSEs’ managers reacted to different kinds of damages based on their ability, knowledge, and experience. Based on research results, managers’ knowledge and skills can help them find more adaptive solutions to keep the firms stable and overcome damages. It can be concluded that Covid-19 pandemic has a great impact on rural MSEs and they need more financial support and managerial advice to overcome this kind of crisis situation.